Accountability in Smart Cities: A Systematic Review of Principles, Components, Monitoring Mechanisms, Challenges, and Improvement Strategies - yudea; Irianto, Gugus; Rusydi, Muhammad Khoiru; Rosidi (Accounting Department,, 2025)
Purpose — This research analyzes the implementation of accountability in the context of smart cities, focusing on principles, components, monitoring mechanisms, implementation challenges, and improvement strategies. The aim is to understand the implementation of accountability comprehensively, address the research gap regarding integrated accountability frameworks, and provide insights to improve smart city governance through strengthening accountability. Poor accountability in smart city initiatives can lead to significant financial inefficiencies and misallocations of public resources. Design/methodology/approach — The research adopted a systematic literature review approach by searching for articles in six academic databases, including Scopus and Web of Science, using Boolean operators (AND, OR). The study selection process used inclusion and exclusion criteria, followed by data extraction, quality assessment using standardized evaluation criteria, synthesis using NVivo, and reporting according to PRISMA guidelines. Findings — 33 relevant studies were found. The most significant discoveries reveal that accountability principles include transparency, responsibility, justice, and sustainability. Financial dimensions of accountability mechanisms are particularly important in ensuring resource optimization. The main components are transparency, citizen participation, collaboration, data management, and security. Effective monitoring mechanisms were identified, such as technology-based supervision, public participation, and transparency. The findings demonstrate the importance of a comprehensive governance framework and prioritizing accountability. Non-technological factors, such as citizen participation and collaboration, are as important as technological aspects. Practical implications—The research provides specific recommendations for the government to apply the principle of accountability systematically, involve citizens, and utilize technology for transparency and monitoring. These governance frameworks can help mitigate financial risks in smart city projects by ensuring proper resource allocation and preventing mismanagement. The research provides comprehensive insights into smart city accountability. Originality/value — An important finding is the need for a governance framework that prioritizes accountability. Further studies are recommended to explore accountability practices in various contexts, develop practical guidelines, and investigate the role of new technologies in improving smart city accountability. Paper type —Literature Review.